Instrumentasi Viralitas Pada Konten Digital Marketing - Migotuwio, Namuri; Giovanni, Talitha Athaya; Prayogi, Rendy (Jurnal Sains Informatika Terapan, 2025)
This research is motivated by the importance of the vitality of digital marketing content in optimizing promotion and advertising processes, which has been proven to increase sales. Along with the rising use of social media, the production of digital marketing videos has also grown significantly. This study aims to formulate visual instruments in digital marketing video content to achieve an optimal level of virality. The research method employed is qualitative, utilizing content analysis techniques on three advertisements: Marjan’s "Baruna Sang Penjaga Samudera" Part 2 (2023), BCA’s "Don't Know? Kasih No!" (2023), and Livin' by Mandiri’s "Ramadhan" (2025). The analysis integrates graphic design theory with Rebecca Lieb’s Content Marketing framework. The results reveal that to produce viral digital marketing video content, several key elements must be fulfilled: the design should remain consistent with the brand’s visual identity; the use of celebrities, comedy, and representations of everyday life serve as effective approaches; medium shot dominance with 2–3 second cut-to-cut transitions, and brand visuals displayed approximately every 50 seconds, constitute the recommended pattern. Furthermore, storytelling based on contemporary culture that offers solutions to consumer problems, combined with distribution through social media platforms with high engagement levels, has been proven to enhance content virality.